the RESILIENSI RUMAH MAKAN PADANG DI KEC. WALANTAKA SELAMA PANDEMI COVID-19: makan - Feby Arma Putra (Technosience, 2023)
The aim of this research is to describe the strategy for adapting and surviving a pandemic in the midst of a pandemic. The method used in this study is a qualitative descriptive study (ethnomethodological) in Serang. The data collection method used participatory observation, in-depth interviews, and documentation. Data were analyzed using four qualitative research steps. Concluded that; a) the strategy of Padang restaurants in Kec. The way to adapt to changes in the midst of a pandemic is to follow the health protocols recommended by the government, b) The survival strategy used is to change the service pattern.